2014
DOI: 10.3390/ijms151018540
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Encapsidation of Flock House Virus by Auto Assembly of Tobacco Mosaic Virus Coat Protein

Abstract: Tobacco Mosaic virus (TMV) coat protein is well known for its ability to self-assemble into supramolecular nanoparticles, either as protein discs or as rods originating from the ~300 bp genomic RNA origin-of-assembly (OA). We have utilized TMV self-assembly characteristics to create a novel Flock House virus (FHV) RNA nanoparticle. FHV encodes a viral polymerase supporting autonomous replication of the FHV genome, which makes it an attractive candidate for viral transgene expression studies and targeted RNA de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 38 publications
(74 reference statements)
1
16
1
Order By: Relevance
“…The advantages of FHV include a bipartite genome, where the polymerase is encoded by the independently replicating RNA 1 and the structural capsid gene is encoded by RNA 2, allowing for easy manipulation of the RNA1 genome for vaccine development and the separation of replication from packaging. We have already tested in vitro assembled TMV-FHV particles and have shown that TMV Oa did not disrupt FHV viral replication, using an enhanced green fluorescent protein (eGFP) transgene to monitor replication and expression in mammalian cells (23). However, the limitations of in vitro encapsidation remain with this system; namely the cost of RNA synthesis and potentially reduced translation due to inefficient in vitro 5' capping.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of FHV include a bipartite genome, where the polymerase is encoded by the independently replicating RNA 1 and the structural capsid gene is encoded by RNA 2, allowing for easy manipulation of the RNA1 genome for vaccine development and the separation of replication from packaging. We have already tested in vitro assembled TMV-FHV particles and have shown that TMV Oa did not disrupt FHV viral replication, using an enhanced green fluorescent protein (eGFP) transgene to monitor replication and expression in mammalian cells (23). However, the limitations of in vitro encapsidation remain with this system; namely the cost of RNA synthesis and potentially reduced translation due to inefficient in vitro 5' capping.…”
Section: Introductionmentioning
confidence: 99%
“…A plasmid (pMT/V5-His A) containing the full FHV RNA1 genome and a ribozyme sequence derived from hepatitis delta virus (HDV) attached to its 3′ end was kindly provided by Professor Ronald Van Rij (Radboud Institute for Molecular Life Sciences, Nijmegen, Netherlands) ( Figure 2A ). Based on Maharaj et al (2014) , an insertion site was created at position 3037 bp of the pMT-FHV RNA1 genome for the introduction of the reporter gene ( eGFP ) and subsequently a D. melanogaster target gene sequence for dsRNA production during viral replication. First, a polylinker, ATGCATGCGATCGCTGTACA, composed of three restriction sites, NsiI, AsiSI, and BsrGI was inserted into position 3037 bp of the pMT-FHV RNA1 genome ( Figure 2B ).…”
Section: Methodsmentioning
confidence: 99%
“…By including origins of assembly (ori) from TMV into the Flock house virus genome, a pseudovirus consisting of the FHV genome encapsidated by TMV coat protein was generated. Since TMV behaves like an adjuvant and can stimulate an immune response, this pseudovirus approach can be used to produce novel vaccines from plants [ 80 ].…”
Section: Merging Of Expression Systems Using Two Different Plant Vmentioning
confidence: 99%